Health-related Quality of Life After Robotic-assisted vs Open Radical Cystectomy: Analysis of a Randomized Trial. Issue 5 (1st May 2023) - Clements, Matthew B.; Beech, Benjamin B.; Atkinson, Thomas M.; Dalbagni, Guido M.; Li, Yuelin; Vickers, Andrew J.; Herr, Harry W.; Donat, S. Machele; Sjoberg, Daniel D.; Tin, Amy L.; Coleman, Jonathan A.; Rapkin, Bruce D.; et al.
Abstract : Purpose: We compare health-related quality of life using a broad range of validated measures in patients randomized to robotic-assisted radical cystectomy vs open radical cystectomy. Methods: We retrospectively analyzed patients that had enrolled in both a randomized controlled trial comparing robotic-assisted laparoscopic radical cystectomy vs open radical cystectomy and a separate prospective study of health-related quality of life. The prospective health-related quality of life study collected 14 patient-reported outcomes measures preoperatively and at 3, 6, 12, 18, and 24 months postoperatively. Linear mixed-effects models with an interaction term (study arm×time) were used to test for differences in mean domain scores and differing effects of approach over time, adjusting for baseline scores. Results: A total of 72 patients were analyzed (n=32 robotic-assisted radical cystectomy, n=40 open radical cystectomy). From 3-24 months post-radical cystectomy, no significant differences in mean scores were detected. Mean differences were small in the following European Organization for Research and Treatment of Cancer QLQ-C30 (Core Quality of Life Questionnaire) domains: Global Quality of Life (−1.1; 95% CI −8.4, 6.2), Physical Functioning (−0.4; 95% CI −5.8, 5.0), Role Functioning (0.7; 95% CI −8.6, 10.0). Mean differences were also small in bladder cancer–specific domains (European Organization for Research and Treatment of Cancer QLQ-BLM30 [Muscle Invasive Bladder Cancer Quality of Life Questionnaire]): Body Image (2.9; 95% CI −7.2, 13.1), Urinary Symptoms (8.0; 95% CI −3.0, 19.0). In Urostomy Symptoms, there was a significant interaction term ( P < .001) due to lower open radical cystectomy scores at 3 and 24 months. Other domains evaluating urinary, bowel, sexual, and psychosocial health-related quality of life were similar. Conclusions: Over a broad range of health-related quality of life domains comparing robotic-assisted radical cystectomy and open radical cystectomy, there are unlikely to be clinically relevant differences in the medium to long term, and therefore health-related quality of life over this time period should not be a consideration in choosing between approaches.